Tricritical curve of massive chiral Gross-Neveu model with isospin - Thies, Michael (Physical Review D, 2022)
We reconsider the two-flavor version of the massive chiral Gross-Neveu model in 1+1 dimensions. Its phase diagram as a function of baryon chemical potential, isospin chemical potential, and temperature has previously been explored. We recapitulate the results, adding the missing tricritical curves. They can be determined exactly by extending the standard stability analysis, using fourth-order almost degenerate perturbation theory. Results for three different bare masses are presented and discussed.
CRIS-Team Scopus Importer:2022-10-21